2022
DOI: 10.1038/s41591-022-01683-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and target engagement of an oral small-molecule sequestrant in adolescents with autism spectrum disorder: an open-label phase 1b/2a trial

Abstract: urrent estimates of ASD prevalence reach one in 54 children born in the United States 1 , and recent clinical failures [2][3][4][5][6][7][8][9] highlight the need to expand drug development efforts. Behavioral features and severity are measured by validated observational assessment tools, as there are no imaging-based or molecular biomarkers that reliably and objectively diagnose ASD. Furthermore, autism manifests across a broad spectrum, from minimally affected individuals to those who require intense support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 111 publications
(108 reference statements)
0
30
0
Order By: Relevance
“…While recent advances indicate that alterations of bacteria or microbiota-derived metabolites modulate neurological disorders 76 , insufficient understanding of the potential targets of microbial products largely limits novel therapy development and clinical translation. Notably, microbiota-based therapeutics have been employed to treat autism spectrum disorder 77 , which serve as a proof of principle that other novel therapies for brain health, including AD, may also be derived by targeting microbiota dysbiosis. In our study, we developed a conceptual ML-based structural systems pharmacogenomics framework based on cheminformatics and bioinformatics data.…”
Section: Discussionmentioning
confidence: 99%
“…While recent advances indicate that alterations of bacteria or microbiota-derived metabolites modulate neurological disorders 76 , insufficient understanding of the potential targets of microbial products largely limits novel therapy development and clinical translation. Notably, microbiota-based therapeutics have been employed to treat autism spectrum disorder 77 , which serve as a proof of principle that other novel therapies for brain health, including AD, may also be derived by targeting microbiota dysbiosis. In our study, we developed a conceptual ML-based structural systems pharmacogenomics framework based on cheminformatics and bioinformatics data.…”
Section: Discussionmentioning
confidence: 99%
“…AB-2004 is a spherical carbon adsorbent with a high surface area that is highly effective in removing uremic toxins, including those produced by gut bacteria. After 8 weeks of treatment with AB-2004, children with ASD showed improvements in anxiety, irritability, and gastrointestinal health [ 165 ].…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%
“…The microbiota-gut-brain axis modulates the body’s response to changes in the microbiota within the gastrointestinal (GI) tract, influencing gut function, bodily immune response, physiological stress and cognitive behaviour. Several studies indicate these complex interacting pathways are disturbed in neurodevelopmental disorders including autism spectrum disorder (ASD; autism) (Campbell et al 2022 ; Matta et al 2019 ; Mayer et al 2014 ; Sharon et al 2019 ; Morais et al 2021 ; Hughes et al 2018 ). Central to our understanding of the cellular basis for the microbiota-gut-brain axis is the gut-associated lymphoid tissue (GALT), a major component of the immune system, comprising multiple lymphoid masses located in the small intestine (i.e., Peyer’s patches), the appendix/caecum (i.e., caecal patch tissue) as well as in the large intestine and rectum.…”
Section: Introductionmentioning
confidence: 99%
“…As such, alterations in host, including changes in nervous system function and patterns of innervation, can influence the development and function of Peyer’s patches and caecal patch tissue. Furthermore, Liu and colleagues reported that host genetics could modify the microbiome (Liu et al 2016 ; Goodrich et al 2014 ), while recent compelling data indicate that modifications to gut microbial metabolites can lead to changes in brain structure and behaviour in the context of autism (Needham et al 2022 ; Campbell et al 2022 ). These recent studies altogether suggest that the microbiota-gut-brain axis, which includes the sensing of microbes and pathogens via GALT signalling, likely play important roles in neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%